THE SUBJECT OF ADMINISTRATIVE LAW: STATE AND PROBLEMS OF RESEARCH - Kunev, Yurii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
The purpose of the article is to formulate problems and determine the theoretical foundations of their solution regarding the definition and research of the object and subject of administrative law. Research methods: a comprehensive approach to creating a theoretical picture of the object and objects and the knowledge that describes and depicts them; comparative legal and doctrinal knowledge of administrative legislation, as well as a method of generalization and modeling of new theoretical knowledge of administrative law. Results: the problems of the further development of legal support of administrative activity are identified and the viewpoints of scientists on the subject of administrative law are summarized. It is substantiated that the approaches to defining the subject of administrative law existing in the majority of domestic scientific works do not entail the application of modern general scientific methodology. Discussion: the proposition that the system of contradictions of administrative law and legislation is directly related to the correct definition of the object and subjects of administrative law is argued. Changes in the definition of the subject of the administrative law of Ukraine should be based on a scientific approach, which includes the definition of the object, the separation of subjects and the application of methodology, which would create the basis for the transition of the administrative law of Ukraine to a new level of development. A significant number of scientific works highlight the issue of defining the subject of administrative law. The same scientists emphasize that administrative law and legislation need significant changes, without indicating the scientific basis of changes that will contribute to the development of administrative law. The problems that exist in administrative legislation in the works of scientists are not directly related to the problems of forming the theoretical and methodological scientific basis of administrative law. It is possible to solve the problems of scientific foundations by using new scientific approaches to determining the foundations of the theory and by formulating the problems in such a way that the ways of solving them are, perhaps not simple, but sufficiently obvious. Such a task is always faced by science, in general, and branch science, in particular. In addition, the modern system of administrative law of Ukraine has not received a stable form, where its main components are connected by ties: the administrative realm; administrative activity; Administrative Law; administrative legislation; administrative procedure; administrative proceedings. Each of the components is separated, with a weak connection to each other.